Analyzing the Impact of Liquidity and Solvency Ratios on Profitability Ratios in FMCG Companies Listed on the Indonesia Stock Exchange from 2014 to 2023 - Dhea Bunga Annisa (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2025)
This study aims to investigate the impact of liquidity and solvency measures on profitability ratios in fast-moving consumer goods (FMCG) firms listed on the Indonesia Stock Exchange.  This research employs a descriptive verification methodology utilizing a quantitative approach.  The utilized data are secondary data sourced from the companies' financial reports throughout the study period.  To verify that the regression model is optimal, linear, unbiased, and efficient, several classical assumption tests were performed prior to further investigation. The findings indicate that the liquidity ratio has a partial, positive, and significant impact on profitability ratios.  This condition suggests that a company's enhanced capacity to fulfill its short-term liabilities is correlated with an increased possibility of profit development.  Conversely, the solvency ratio has a negative and considerable influence on profitability ratios, suggesting that a substantial debt burden may hinder a company's ability to generate profits.  The liquidity ratio and solvency ratio have a significant impact on corporate profitability.  These findings underscore the significance of effective liquidity management and capital structure in sustaining a company's financial performance and enhancing its profitability.